2021
DOI: 10.36740/wlek202107119
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Hygienic Correlates of Teachers’ Occupational Burnout Syndrome Development

Abstract: The aim: To determine physiological and hygienic correlates of teachers’ occupational burnout syndrome development in general secondary education institutions. Materials and methods: The study involved 427 teachers of general secondary education institutions of Sumy region aged 21 to 71 years old, representing four pedagogical categories. During the study physiological, hygienic, psychological, mathematical and statistical research methods were used. Results: A high level of occupational burnout was found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Regarding the workload, many studies have shown that workload (expressed in our study as long hours spent for preparation of materials to be delivered to the students and teaching preparatory students, who are at the beginning of the teen age and need more time to understand and do better job in studying) was closely related to burnout in the form of emotional exhaustion and depersonalization among teachers, including Saudi teachers (Santana et al, 2012;Chalghaf et al, 2019;Amri et al, 2020;Salvagioni et al, 2020;Cobo-Vazquez et al, 2021;Kalynychenko et al, 2021;Li et al, 2021;Melanda et al, 2021;Ribeiro et al, 2021). Moreover, the notion of burnout as a response to job demands has been supported by both selfreports of experienced stress and more objective assessments of demands, such as the number of students and number of working hours (Maslach, 2001;Perry et al, 2014;Peterson et al, 2019;Hart et al, 2020;Ndongo et al, 2020;Shah et al, 2021).…”
Section: Discussionmentioning
confidence: 71%
“…Regarding the workload, many studies have shown that workload (expressed in our study as long hours spent for preparation of materials to be delivered to the students and teaching preparatory students, who are at the beginning of the teen age and need more time to understand and do better job in studying) was closely related to burnout in the form of emotional exhaustion and depersonalization among teachers, including Saudi teachers (Santana et al, 2012;Chalghaf et al, 2019;Amri et al, 2020;Salvagioni et al, 2020;Cobo-Vazquez et al, 2021;Kalynychenko et al, 2021;Li et al, 2021;Melanda et al, 2021;Ribeiro et al, 2021). Moreover, the notion of burnout as a response to job demands has been supported by both selfreports of experienced stress and more objective assessments of demands, such as the number of students and number of working hours (Maslach, 2001;Perry et al, 2014;Peterson et al, 2019;Hart et al, 2020;Ndongo et al, 2020;Shah et al, 2021).…”
Section: Discussionmentioning
confidence: 71%
“…Several main areas of PA research can be identified: 1) study of functional changes in the body under the influence of PA; 2) determination of PA norms for different age and gender groups; 3) studying the energy characteristics of PA. Today, the direction of development of the methods of quantitative and qualitative assessment of PA remains relevant. The most widespread are: the method of pedometry, registration of energy expenditure, determination of the time spent during the day, week, month, year on all forms of physical activity, the ratio of dynamic and static components of muscle activity during the day, timing, pulsometry, the method of determining the sum of movements in linear indicators of locomotion, self-control (Polka et al, 2011;Kalynychenko et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of teachers' professional PA indicates a predominantly sedentary lifestyle at the expense of direct professional activity (Bogaert et al, 2014;Kalynychenko, 2021). A study of teachers' PA before the COVID-19 pandemic proves its dependence on the profession.…”
Section: Introduction Problem Statement and Research Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…As a result of exposure to such long-term professional stresses of medium intensity, professional burnout (PB) occurs among pedagogical workers (Prokopenko, 2019;Teles et al, 2020). Scientists analysed the factors leading to the development of professional burnout, studying social, personal, organizational factors and physiological, hygienic correlates of the development of PB (Kalynychenko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%